Logistics processes as a source of competitive advantage - Pszenna, Izabella (My University, 2023)
The following thesis “Logistics processes as a source of competitive advantage” deals with the topic of logistics in the broadest sense and its relation to competitive advantage. This work considers several research questions regarding the supply chain and also many other factors affecting the success of a company in the market. A broad view of the problem helps to understand the complexity of logistics processes and their impact on the overall performance of the company. The thesis focuses on the analysis of how the Biedronka and Pingo Doce supermarkets operate in terms of logistics and competitiveness. The thesis was written based on source materials from Polish and foreign scientific literature in the field of logistics and management. The research method used for the thesis was a case study on Biedronka supermarket and Pingo Doce. Based on the results of the study, a number of factors were found to influence the competitiveness of the company. Starting with the organisational structure, the supply chain or logistics systems that improve the planning and organisation of the distribution of goods, which ultimately translates into efficiency, profits and competitiveness on the market. Modern companies, striving for market success, should use the potentials inherent in logistics. This is a huge field, with many opportunities for achieving competitive advantage today and in the future.
Keywords: Logistics; Logistics processes competitiveness; Competitive advantage; Supply chain